Maternal inflammation during pregnancy and offspring psychiatric symptoms in childhood: Timing and sex matter. (April 2019) - Mac Giollabhui, Naoise; Breen, Elizabeth C.; Murphy, Shannon K.; Maxwell, Seth D.; Cohn, Barbara A.; Krigbaum, Nickilou Y.; Cirillo, Piera M.; Perez, Christian; Alloy, Lauren B.; Drabick, Deborah A.G.; Ellman, Lauren M.
Abstract: Objective: Maternal infection during pregnancy has been associated with increased risk of offspring psychopathology, including depression. As most infections do not cross the placenta, maternal immune responses to infection have been considered as potentially contributing to this relationship. This study examined whether gestational timing of maternal inflammation during pregnancy is associated with offspring internalizing and/or externalizing symptoms during childhood and, further, whether fetal sex moderated this relationship. Method: Participants were 737 pregnant women and their offspring who were continuously followed through late childhood. Archived first and second trimester sera were analyzed for markers of inflammation [interleukin 8 (IL-8), IL-6, IL-1 receptor antagonist (IL-1ra), and soluble tumor necrosis factor receptor-II (sTNF-RII)]. When offspring were aged 9–11, mothers completed a questionnaire assessing psychological symptoms. Results: Multivariate regression analyses indicated that elevated IL-8 in the first trimester was associated with significantly higher levels of externalizing symptoms in offspring. Higher IL-1ra in the second trimester was associated with higher offspring internalizing symptoms. Further, second trimester IL-1ra was associated with increased internalizing symptoms in females only. Conclusion: These findings demonstrate that elevated maternal inflammation during pregnancy is associated with the emergence of separate psychological phenotypes and that timing of exposure and fetal sex matter for offspring outcomes. Given that internalizing and externalizing symptoms in childhood increase risk for a variety of mental disorders later in development, these findings potentially have major implications for early intervention and prevention work.